2017
DOI: 10.1002/bjs5.3
|View full text |Cite
|
Sign up to set email alerts
|

Development of incisional herniation after midline laparotomy

Abstract: BackgroundIncisional herniation is a common complication after abdominal surgery associated with considerable morbidity. The aim of this study was to determine whether incisional hernia is an early complication, in order to understand better the aetiology of incisional hernia formation.MethodsThis study involved the secondary analysis of a subset of patients included in a large RCT comparing small and large tissue bites (5 mm every 5 mm, or 1 cm every 1 cm) in patients scheduled to undergo elective abdominal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…A total of 5 high-quality studies were used to generate this review, 4 RCTs, 3 studies showed a statistically significant difference in the incidence of incisional hernia in favour of the small bite technique, but in all studies the incidence was higher in the large bite group. All studies have large sample size, and 3 were double-blinded and multicentric, while the other 3 studies [ 4 , 5 ] were single centre and not blinded. Follow up period of 12 months amongst most the studies was relatively short, given that incisional hernia can develop years after primary operation [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 5 high-quality studies were used to generate this review, 4 RCTs, 3 studies showed a statistically significant difference in the incidence of incisional hernia in favour of the small bite technique, but in all studies the incidence was higher in the large bite group. All studies have large sample size, and 3 were double-blinded and multicentric, while the other 3 studies [ 4 , 5 ] were single centre and not blinded. Follow up period of 12 months amongst most the studies was relatively short, given that incisional hernia can develop years after primary operation [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…[15] The incidence of incisional hernia is significantly lower in small-bite closure than large-bite closure in other studies found in the literature. [13,16]…”
Section: Discussionmentioning
confidence: 99%
“…In hand surgery, a gap formation of 2 mm is associated with tendon ruptures and scarring. Similarly, 12 mm of gapping of a laparotomy closure over the first 30 days after repair is associated with a 94% chance of incisional hernia formation [43].…”
Section: Mesh Suturementioning
confidence: 99%